Stratification of G2 pancreatic neuroendocrine tumors using a Ten Percent Ki-67 index cut-off based on clinicopathological and molecular analyses - Yumiko Kageyama; Ryo Ashida; Nobuyuki Ohike; Keiichi Ohshima; Tomoko Norose; Katsuhisa Ohgi; Mihoko Yamada; Shimpei Otsuka; Yoshiyasu Kato; Hidemasa Kubo; Katsuhiko Uesaka; Teiichi Sugiura; et al. (Scientific Reports)
Abstract Pancreatic neuroendocrine tumors (PanNETs) often have low malignancy, but some develop distant metastasis or recurrence. This study aimed to investigate the prognostic utility of a Ki-67 index 10% cut-off using clinicopathological and multiomics analyses. Eighty-seven resected PanNETs were classified as G1, G2-low, G2-high, and G3 according to the World Health Organization classification, incorporating a 10% Ki-67 threshold. These groups comprised 29 (33%), 33 (38%), 16 (18%), and 9 (10%) patients, respectively. Comprehensive analyses evaluated tumor characteristics and mutation profiles across the groups. Significant differences in tumor size, recurrence, and overall survival were observed between the G2-low and G2-high groups. Genomic profiling of 19 samples revealed that the G3 (4 patients) and G2-high (6 patients) groups showed greater tumor mutation burdens and more driver gene mutations than the G2-low (6 patients) and G1 (3 patients) groups. Gene expression profiling revealed distinct patterns between the G3/G2-high and G2-low/G1 groups, with the oncogene SERPINA1 significantly upregulated in the G3/G2-high group. The multiomics approach identified key genes, emphasizing the significance of the Ki-67 index 10% cut-off in predicting tumor behavior. The findings support using the Ki-67 index of 10% as a critical threshold for stratifying PanNETs and guiding prognosis and treatment.